OPTIMIZING STUDENTS’ BLOG BASED ONLINE BUSINESS BY UTILIZING GOOGLE KEYWORD PLANNER AND GOOGLE TRENDS - Ellisa Indriyani (Universitas Ahmad Dahlan)
This paper aims to describe the search engine optimization of students’ blog based business by utilizing Google Keyword Planner and Google Trends. Students’ blog based business is one of activities employing content writing in Business English Writing Class. It is a blog based project. As a matter of fact, most of the blog based project ended up underutilized. Producing content writing is not that simple, besides the writing quality, students have to make sure that the writing product can be searched online and indexed by Google. Thus, not only having an excellent writing skill and qualified products, students also have to learn how to optimize their content writing. This study employs a descriptive qualitative method in term of case study. Subjects are Business English Writing Class students in English Education Department of Sebelas Maret University. The findings reveal that: 1) the students’ content writing have good quality, good optimization and resulted in the real transactional activities; 2) the students acknowledge that they have to conduct a mini research to figure out what is the most appropriate keyword elaborated in their writing used in promoting their products; 3) the students learn that blog based writing is not only substituting from paper based writing into internet based writing.